Preparation method and application of friction nanometer power generation yarn and fabric with good flame retardance and smoke suppression performance

By using a composite yarn structure composed of flame-retardant polyester filaments and polytetrafluoroethylene filaments in the friction nano-powered fabric, the problem of insufficient flammability in the prior art is solved, and high flame retardancy and electrical output are achieved The performance improvement is suitable for applications such as smart fire suits and escape blankets.

CN119194687APending Publication Date: 2024-12-27BEIJING INST OF CLOTHING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410802337.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-26
Filing Date
2024-06-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing friction nano-powered fabrics are not flammable enough, making it difficult to maintain power supply capacity in fires, and may induce fire spread and lead to personnel injury.

Method used

Using composite yarn structure, the inner core is silver-plated nylon filaments, and the outer friction layer is composed of flame-retardant polyester filaments and polytetrafluoroethylene filaments. Through specific fineness and component ratios, metal organic framework materials (MOFs are added. ) and flame retardant, composite yarns with leather core structure are prepared, and a flame retardant and smoke-resisting friction nano-powered fabric is formed through high-speed weaving technology.

Benefits of technology

It achieves good flame retardant performance and electrical output performance of friction nano-powered fabrics, has excellent cycle working stability and water washing resistance, and is suitable for intelligent protective clothing and intelligent escape blankets, ensuring safety and reliability under fire conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194687A_ABST
    Figure CN119194687A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of friction nanometer power generation yarn and fabric with good flame retardance and smoke suppression performance, and belongs to the technical field of spinning. The flame-retardant polyester filaments and the polytetrafluoroethylene filaments are woven on the outer side of the silver-plated nylon yarn to form the outer friction layer, the skin-core structure composite yarn containing the conductive inner core is prepared, then the friction nanometer power generation fabric with good flame-retardant and smoke-suppression performance is prepared through weaving, the obtained fabric is excellent in flame-retardant performance and electric output performance, and the fabric is good in flame-retardant and smoke-suppression performance. And the fabric shows excellent cycle working stability and washing resistance, is high in air and moisture permeability and good in comfort, and can be used in intelligent protective clothing and intelligent escape blankets.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention claims the priority of the Chinese patent application filed with the China Patent Office on June 26, 2023, with application number 202310760880.1 and invention name “A method for preparing friction nano-power generation fabric with good flame retardant and smoke suppression properties”, the entire contents of which are incorporated by reference in the application. Technical Field

[0002] The invention belongs to the field of textile technology, and specifically relates to a preparation method and application of a friction nano-generated electricity yarn and fabric with good flame retardancy and smoke suppression. Background Art

[0003] As an important branch of smart materials, wearable smart sensing materials have great application potential in the fields of human body sensing, artificial intelligence, medical bionics, etc., and will provide unlimited possibilities for human motion monitoring, health testing, etc., so they have received widespread attention from domestic and foreign academic circles. Smart wearable fabrics have the characteristics of light weight, low modulus, high softness and elasticity, multi-dimensional structure, low cost, and high skin affinity. Compared with smart bracelets, smart glasses, smart skin and other sensing devices, they have unique advantages in the field of smart wearables. The development of self-powered sensing fabrics that do not require external power is one of the important development directions of smart wearable fabrics today. It is not only conducive to energy conservation, but also will greatly improve the portability, comfort and long-term use of the equipment in practical applications, which has important research significance.

[0004] Using the friction electrification (contact electrification) effect, Professor Wang Zhonglin proposed the concept of friction nanogenerator (TENG). TENG can generate electrical signals under external pressure, thereby converting mechanical energy into electrical energy. Combining TENG with traditional textiles, researchers have developed friction nanogenerator fabric (TTENG). TTENG combines the piezoelectric effect of TENG with the soft, breathable and comfortable properties of textiles. It has outstanding application prospects in the field of smart textiles and smart wearables, and has attracted widespread attention from researchers at home and abroad. For example, patent CN114836873A discloses a gecko bionic nanofiber fleece friction power generation fabric with self-cleaning and self-powered functions and its preparation method, which includes: first preparing polyisophthalamide and PVA solution, then using polyisophthalamide as islands and PVA as seas, and obtaining composite yarns through composite spinning at a certain sea island ratio; using composite yarns as warp yarns and conductive yarns as weft yarns to weave it into plain fabrics, and repeatedly kneading the fabrics to obtain stable and dense fluff; then immersing it in water to fully disperse PVA in water, heating it to dissolve PVA, and obtaining nanofiber fleece fabrics with sea island structure; finally, placing it in a silane coupling agent for treatment to obtain super hydrophobic self-cleaning fabrics. The high contact area characteristics of nano-aramid fiber fleece similar to the fluff on the soles of geckos are used to maximize the friction area, and the piezoelectric effect is produced during the touch and pressure process, thereby improving the friction power and the sensitivity of the touch and pressure induced voltage. Patent CN109123854A discloses a friction nano-power generation fabric, including a first conductive yarn electrode, a second conductive yarn electrode, a first conductive fabric, a second conductive fabric and a non-conductive yarn fabric. It has good wearing properties such as air permeability and moisture permeability, can be fully integrated with clothing, can power small electronic devices, and can also be used to build self-driven sensors for human motion pattern recognition and other purposes.

[0005] However, due to the flammability of textile materials, most TTENGs currently do not have flame retardant properties and are easily damaged in fires, losing power supply capabilities, and even further inducing the spread of fires and causing personal injury. Therefore, it is crucial to design and manufacture TTENGs with high flame retardancy and smoke suppression properties. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a friction nano-generated power yarn and fabric with good flame retardancy and smoke suppression and its application in view of the deficiencies of the prior art. The method is simple, and the obtained friction nano-generated power fabric has excellent flame retardancy and electrical output performance, and exhibits excellent cycle working stability and water washability, high air permeability and moisture permeability, and good comfort, and can be used in intelligent protective clothing and intelligent escape blankets.

[0007] A composite yarn has a sheath-core structure, wherein the sheath-core structure consists of an inner core and an outer friction layer, wherein the inner core is a silver-plated nylon filament, and the outer friction layer comprises a flame-retardant polyester filament and a polytetrafluoroethylene filament.

[0008] Furthermore, in one composite yarn, the total number of the flame-retardant polyester filaments and the polytetrafluoroethylene filaments is 8, and the flame-retardant polyester filaments and the polytetrafluoroethylene filaments are selected from 1 to 7, respectively. Preferably, the number of the flame-retardant polyester filaments is 4 and the number of the polytetrafluoroethylene filaments is 4, or the number of the flame-retardant polyester filaments is 3 and the number of the polytetrafluoroethylene filaments is 5.

[0009] The fineness of the silver-plated nylon filament is 20-200D, preferably 20-100D.

[0010] The fineness of the flame retardant polyester filament is 50-200D, preferably 100-150D.

[0011] The fineness of the polytetrafluoroethylene filament is 300-600D, preferably 450-550D.

[0012] The flame retardant polyester filament comprises polymerization monomers, MOFs and a flame retardant.

[0013] Wherein, the MOFs is the abbreviation of Metal Organic Frameworks.

[0014] Furthermore, in the flame-retardant polyester filament, the amount of MOFs is 1-5% of the mass of the polymerized monomer, and the amount of the flame retardant is 0.5-5% of the mass of the polymerized monomer; preferably, the amount of MOFs is 1.5-3% of the mass of the polymerized monomer, and the amount of the flame retardant is 2-3% of the mass of the polymerized monomer.

[0015] Furthermore, the polymerizable monomers include aromatic dicarboxylic acids or their ester derivatives and aliphatic diols, wherein the molar ratio of the aromatic dicarboxylic acids or their ester derivatives to the aliphatic diols is 1.3-1.8:1, and preferably 1.4-1.55:1.

[0016] Furthermore, the aromatic dicarboxylic acid or its ester derivative refers to an aromatic dicarboxylic acid having 8 to 12 carbon atoms or its alkyl ester, selected from any one or more of terephthalic acid, phthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid and 2,7-naphthalene dicarboxylic acid; preferably any one or more of terephthalic acid, phthalic acid and isophthalic acid.

[0017] Furthermore, the aliphatic diol refers to an aliphatic diol having 2 to 6 carbon atoms, selected from any one or more of ethylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol and tripropylene glycol; preferably any one or more of ethylene glycol, 1,3-propylene glycol, 1,3-butanediol, diethylene glycol and dipropylene glycol.

[0018] Further, the MOFs are selected from any one or more of iron-based MOFs, magnesium-based MOFs, zinc-based MOFs, cobalt-based MOFs, copper-based MOFs, hafnium-based MOFs and lanthanide metal-based MOFs, preferably cobalt-based MOFs. As an example of the present invention, the MOFs is ZIF-67 (2-methylimidazole cobalt).

[0019] Furthermore, the flame retardant is selected from any one or more of a carbon-based flame retardant, a phosphorus-based flame retardant and a nano inorganic flame retardant.

[0020] Furthermore, the phosphorus-based flame retardant refers to a flame retardant containing one or more hydroxyl or carboxyl or carboxylate groups or phosphate groups, selected from any one or a mixture of triphenyl phosphate, triaryl phosphate, aromatic phosphate, 2-ethylhexyl diphenyl phosphate, tricresyl phosphate, 2-carboxyethyl phenyl hypophosphorous acid, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide and 6-oxo-6H-dibenzo-c,e-1,2-oxaphosphahexanin-6-onemethyl-succinic acid; preferably any one or more of 2-ethylhexyl diphenyl phosphate, tricresyl phosphate and 2-carboxyethyl phenyl hypophosphorous acid.

[0021] Furthermore, the carbon-based flame retardant is a flame retardant based on carbon compounds or carbon-containing macromolecular materials, preferably nanographene and / or carbon nanotubes.

[0022] Furthermore, the nano inorganic flame retardant is selected from any one or more of nano aluminum hydroxide, nano magnesium hydroxide, nano montmorillonite, nano zinc borate, nano talc and nano calcium sulfate, preferably nano talc and / or nano magnesium hydroxide.

[0023] Preferably, the flame retardant is a carbon-based flame retardant, a phosphorus-based flame retardant and a nano inorganic flame retardant in a mass ratio of 1:0.5-1:0.2-0.5, and more preferably is tritolyl phosphate, carbon nanotubes and nano talc in a mass ratio of 1:0.6-0.8:0.3-0.4.

[0024] The flame retardant polyester filament is prepared by the following method:

[0025] After the polymerization monomer undergoes esterification reaction, MOFs and flame retardants are added in proportion, and then a polycondensation catalyst is added to carry out polycondensation reaction to obtain polyester; finally, spinning is performed to obtain flame-retardant polyester filaments.

[0026] Furthermore, the esterification reaction temperature is 230-260°C, and the reaction time is 1-4h; preferably, the esterification reaction temperature is 240-250°C, and the reaction time is 2-3h.

[0027] Furthermore, the polycondensation catalyst is any one or more of antimony-based, germanium-based, titanium-based and tin-based catalysts, preferably an antimony-based catalyst.

[0028] Furthermore, the amount of the catalyst used is 0.01-0.5% of the mass of the polymer monomer, preferably 0.1-0.2% of the mass of the polymer monomer.

[0029] Further, in the spinning process, the spinning temperature is 260-275° C., the spinning speed is 1000-3000 m / min, the drawing temperature is 60-80° C., the drawing multiple is 1.5-3.4 times, and the setting temperature is 170-190° C. Preferably, in the spinning process, the spinning temperature is 270-275° C., the spinning speed is 1800-2000 m / min, the drawing temperature is 70-75° C., the drawing multiple is 2-3 times, and the setting temperature is 175-185° C.

[0030] On the other hand, the method for preparing the composite yarn comprises the following steps:

[0031] The flame-retardant polyester filament and PTFE filament are pre-wound on the yarn tube, and the silver-plated nylon filament is wound on a special bobbin in the middle of the high-speed braiding machine, fed axially from below the track disk, the gear transmission ratio is set, and then the machine is turned on for spinning to obtain a composite yarn with a skin-core structure.

[0032] Furthermore, the gear transmission ratio is 0.3-0.5, preferably 0.3-0.35.

[0033] On the other hand, a friction nano-electricity generating fabric with good flame retardancy and smoke suppression is woven from the above-mentioned composite yarn.

[0034] On the other hand, the composite yarn or the friction nano-power generation fabric with good flame retardancy and smoke suppression is used in smart firefighting clothing and smart escape carpets.

[0035] Beneficial effects:

[0036] (1) The present invention uses high-speed weaving technology to weave flame-retardant polyester filaments and polytetrafluoroethylene filaments on the outside of silver-plated nylon yarns to construct an outer friction layer, forming a skin-core structure composite yarn containing a conductive inner core, and then weaving to obtain a friction nano-power generation fabric with good flame retardancy and smoke suppression. The resulting fabric has excellent flame retardant properties and electrical output performance, and exhibits excellent cyclic working stability and water washability, high air permeability and moisture permeability, and good comfort.

[0037] (2) Compared with the composite yarn made of flame-retardant polyester filaments as the outer friction layer, the composite yarn made of flame-retardant polyester filaments and polytetrafluoroethylene filaments as the outer friction layer of the present invention has higher electrical output performance and flame retardant performance, and has excellent cycle working stability and water washing resistance, and high air permeability and moisture permeability; controlling the ratio of flame-retardant polyester filaments to polytetrafluoroethylene filaments can further improve the flame retardant performance of the composite yarn.

[0038] (3) The present invention uses aromatic dicarboxylic acids or their ester derivatives and aliphatic diols as polymerization monomers, adds MOFs and flame retardants to prepare flame-retardant polyester filaments, and adjusts the amount of each component to enable the flame-retardant polyester filaments to obtain excellent moisture absorption and air permeability and flame retardant properties; through the coordinated use of MOFs and specific flame retardants, the electronegativity of the flame-retardant polyester filaments can be improved, which is beneficial to improving the electrical output performance of the composite yarn. In addition, it also has a significant gain effect on the flame retardant and mechanical properties of the composite yarn, which helps to improve the overall performance of the fabric.

[0039] (4) In the process of preparing the composite yarn, the present invention helps to improve the mechanical properties of the composite yarn by adjusting the gear ratio of the high-speed braiding machine.

[0040] (5) The composite yarn or friction nano-electricity generating fabric obtained by the present invention can be worn on the human body to monitor the movement of human limbs, thereby meeting the self-powered sensing requirements of smart firefighting suits; it can also be used as a flame-retardant self-powered pressure sensing fabric and applied to smart escape carpets. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of the weaving of the composite yarn of Example 1 of the present invention.

[0042] Figure 2 1 is a SEM image of the composite yarn of Example 1 of the present invention; in the image, (a) is a surface image, and (b) is a cross-sectional image.

[0043] Figure 3 1 is an optical microscope image of the composite yarn prepared under different gear transmission ratio conditions of the present invention; in the image, (i) the gear transmission ratio is 0.3, (ii) the gear transmission ratio is 0.35, (iii) the gear transmission ratio is 0.4, (iv) the gear transmission ratio is 0.45, and (v) the gear transmission ratio is 0.5.

[0044] Figure 4 Schematic diagram of the flame retardant and smoke suppression performance test results of the composite yarn of the present invention; in the figure, (a) heat release rate curve, (b) total heat release curve.

[0045] Figure 5 1 is a schematic diagram of the electrical output performance test results of the fabric of Example 1 of the present invention at different frequencies; in the figure, (a) V OC ; (b) I SC ; (c) Q SC .

[0046] Figure 6 It is a schematic diagram of the change of current and power density of the fabric of Example 1 of the present invention with load resistance.

[0047] Figure 7 It is a schematic diagram of the test results of the electrical output performance of the fabrics of Example 1 of the present invention and Comparative Example 4.

[0048] Figure 8 It is a schematic diagram of the friction nano-electricity generating fabric of Example 1 of the present invention applied to the intelligent fire-fighting clothing, which reflects the open circuit voltage detection effect of detecting the body movements of firefighters with different amplitudes.

[0049] Fig. 9 This is a schematic diagram of the friction nano-electric power generation fabric of Example 1 of the present invention applied to the smart escape carpet; wherein, a is a schematic diagram of the working of the smart escape carpet. When the escape carpet is stepped on by a person, the generated electricity is used to supply the light of the emergency indicator light; b is a photo of the performance process of the smart escape carpet in the laboratory. DETAILED DESCRIPTION

[0050] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present invention.

[0051] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.

[0052] In the following examples, the carbon nanotube manufacturer is Mitsubishi-Kumho Chemical Co., Ltd., and the specifications are less than 5 μm in length and 10-15 nm in diameter; the nano talc manufacturer is Dandong Yongxing Mining Co., Ltd., and the specifications are industrial grade 2500 mesh.

[0053] Example 1

[0054] A composite yarn (FR-PET&PTFE FTENG), each composite yarn has a silver-plated nylon filament as an inner core, four flame-retardant polyester filaments (FR-PET) and four polytetrafluoroethylene (PTFE) filaments to form an outer friction layer, and the outer film friction layer is wrapped on the outside of the inner core.

[0055] The fineness of the silver-plated nylon filament is 20D.

[0056] The fineness of the flame retardant polyester filament is 150D.

[0057] The fineness of the PTFE filament is 500D.

[0058] The flame retardant polyester filament is prepared by the following method:

[0059] The polymer monomers aromatic dicarboxylic acid and aliphatic diol are mixed in a molar ratio of 1.5:1, and esterification reaction is carried out at 240°C for 3 hours. Then, MOFs (2% of the total mass of the polymer monomers) and flame retardants (2% of the total mass of the polymer monomers) are added, and then a polycondensation catalyst (0.1% of the total mass of the polymer monomers) is added to carry out a polycondensation reaction to obtain polyester; then spinning is carried out to obtain flame-retardant polyester filaments, the spinning temperature is 260°C, the spinning speed is 2000m / min, the drawing temperature is 75°C, the drawing multiple is 3 times, and the setting temperature is 170°C.

[0060] In this embodiment, the aromatic dicarboxylic acid is terephthalic acid, the aliphatic diol is dipropylene glycol, the flame retardant is a phosphorus flame retardant, a carbon-based flame retardant and an inorganic nano flame retardant, specifically tritolyl phosphate, carbon nanotubes and nano talc in a mass ratio of 1:0.7:0.3, and the polycondensation catalyst is antimony trioxide.

[0061] In this embodiment, the MOFs used is ZIF-67 (2-methylimidazole cobalt), and its preparation method is the preparation method of ZIF-67 described in Example 1 of patent CN117903581A.

[0062] This embodiment also provides a method for preparing the composite yarn, comprising the following steps:

[0063] Pre-wind the flame-retardant polyester filament and PTFE filament on the bobbin, wind the silver-plated nylon filament on the special bobbin in the middle of the high-speed braiding machine, feed it axially from the bottom of the track disk, set the gear ratio to 0.3, and then start the machine for spinning to obtain a composite yarn with a core-skin structure. In the composite yarn, the number of silver-plated nylon filaments, flame-retardant polyester filaments, and PTFE filaments is 1, 4, and 4, respectively. The braiding schematic diagram of the composite yarn is shown in FIG. Figure 1 The structure of the composite yarn was observed by scanning electron microscopy, and the surface and cross-sectional SEM images of the composite yarn were measured as shown in Figure 2As shown, it can be seen that the flame-retardant polyester filaments and PTFE filaments are alternately woven on the outside of the silver-plated nylon yarn, tightly wrapping the conductive inner core, so that the composite yarn has an obvious skin-core structure.

[0064] This embodiment also provides a friction nano-electricity generating fabric with good flame retardancy and smoke suppression, which is woven from the above-mentioned composite yarn.

[0065] Example 2

[0066] A composite yarn, each composite yarn has a silver-plated nylon filament as an inner core, three flame-retardant polyester filaments and five PTFE filaments as an outer friction layer, and the outer film friction layer is wrapped on the outside of the inner core.

[0067] The fineness of the silver-plated nylon filament is 40D.

[0068] The fineness of the flame retardant polyester filament is 100D.

[0069] The fineness of the PTFE filament is 550D.

[0070] The flame retardant polyester filament is prepared by the following method:

[0071] Aromatic dicarboxylic acids and aliphatic diols are mixed in a molar ratio of 1.4:1, and esterification reaction is carried out at 250°C for 2h, and then MOFs (3% of the total mass of the polymerized monomers) and flame retardants (3% of the total mass of the polymerized monomers) are added, and then a polycondensation catalyst (0.1% of the total mass of the polymerized monomers) is added to carry out polycondensation reaction to obtain polyester; then spinning is carried out to obtain flame-retardant polyester filaments, the spinning temperature is 275°C, the spinning speed is 1800m / min, the drawing temperature is 70°C, the drawing multiple is 3 times, and the setting temperature is 190°C.

[0072] In this embodiment, the aromatic dicarboxylic acid is phthalic acid, the aliphatic diol is ethylene glycol, the flame retardant is carbon nanotubes, a carbon-based flame retardant, and the polycondensation catalyst is antimony trioxide.

[0073] In this example, the preparation method of the MOFs used is the same as that in Example 1.

[0074] This embodiment also provides a method for preparing the composite yarn, comprising the following steps:

[0075] The flame-retardant polyester filament and the PTFE filament are pre-wound on the bobbin, the silver-plated nylon filament is wound on a special bobbin in the middle of the high-speed braiding machine, and fed axially from the bottom of the track disk, the gear ratio is set to 0.35, and then the machine is turned on for spinning to obtain a composite yarn with a skin-core structure. The composite yarn contains 3 flame-retardant polyester filaments and 5 PTFE filaments. This embodiment also provides a friction nano-power generation fabric with good flame retardancy and smoke suppression, which is made by weaving the above composite yarn.

[0076] Example 3

[0077] Compared with Example 1, 4 flame-retardant polyester filaments and 4 PTFE filaments are replaced by 2 flame-retardant polyester filaments and 6 PTFE filaments, and the rest are the same.

[0078] Example 4

[0079] Compared with Example 1, 4 flame-retardant polyester filaments and 4 PTFE filaments are replaced by 1 flame-retardant polyester filament and 7 PTFE filaments, and the rest are the same.

[0080] Example 5

[0081] Compared with Example 1, 4 flame-retardant polyester filaments and 4 PTFE filaments are replaced by 5 flame-retardant polyester filaments and 3 PTFE filaments, and the rest are the same.

[0082] Example 6

[0083] Compared with Example 1, 4 flame-retardant polyester filaments and 4 PTFE filaments are replaced by 6 flame-retardant polyester filaments and 2 PTFE filaments, and the rest are the same.

[0084] Example 7

[0085] Compared with Example 1, 4 flame-retardant polyester filaments and 4 PTFE filaments are replaced by 7 flame-retardant polyester filaments and 1 PTFE filament, and the rest are the same:

[0086] Comparative Example 1

[0087] The difference from Example 1 is that the gear transmission ratio in the composite yarn preparation process is 0.4, and the rest are the same.

[0088] Comparative Example 2

[0089] The difference from Example 1 is that the gear transmission ratio in the composite yarn preparation process is 0.45, and the rest are the same.

[0090] Comparative Example 3

[0091] The difference from Example 1 is that the gear transmission ratio in the composite yarn preparation process is 0.5, and the rest are the same.

[0092] Comparative Example 4

[0093] Another composite yarn (FR-PET TTENG) is different from Example 1 in that the composite yarn has silver-plated nylon filaments as the inner core and flame-retardant polyester filaments (FR-PET) as the outer friction layer, and the rest are the same.

[0094] Comparative Example 5

[0095] The difference from Example 1 is that the gear transmission ratio in the composite yarn preparation process is 0.35, and the rest are the same.

[0096] Experimental Example 1

[0097] Structural characterization

[0098] The composite yarns prepared in Example 1 and Comparative Examples 1-3 and 5 were observed using an optical microscope, and the tightness of the outer friction layer wrapping is shown in the following Table 1:

[0099] Table 1

[0100] Group The tightness of the outer friction layer Gear Ratio Example 1 tight 0.3 Comparative Example 1 More strict 0.4 Comparative Example 2 More strict 0.45 Comparative Example 3 More strict 0.5 Comparative Example 5 More strict 0.35

[0101] like Figure 3 As shown, it can be seen that when the gear ratio is set to 0.3, the outer friction layer of the obtained composite yarn is most tightly wrapped, which is beneficial to improving the mechanical properties of the composite yarn.

[0102] Experimental Example 2

[0103] Flame retardant properties

[0104] (1) Referring to the method in GB / T5455-1997 standard, the limiting oxygen index (LOI) and vertical burning performance of the fabrics in various embodiments and comparative examples were tested. The results are shown in Table 2 below.

[0105] Table 2

[0106]

[0107]

[0108] The results show that compared with the FR-PET TTENG of Comparative Example 4, the LOI of the FR-PET&PTFE TTENG of Example 1 is significantly higher, and the vertical combustion afterburning time and smoldering time of the FR-PET&PTFE TTENG are 0.8s and 0s, respectively, which are much lower than those of the FR-PET TTENG, and no droplet occurs. It can be seen that the flame retardant performance can be improved by preparing the composite yarn with flame retardant polyester filaments and PTFE filaments as the outer friction layer. In addition, the LOI and damage length values ​​in Example 5 are significantly higher than those in Example 1. It can be seen that when the root number ratio of the flame retardant polyester filaments and the PTFE filaments is within a specific range, it is easier to obtain excellent flame retardant performance.

[0109] (2) The flame retardant and smoke suppression properties of the fabrics in each embodiment and comparative example were tested by cone calorimeter. The test results of embodiment 1 and comparative example 4 are shown in FIG. Figure 4 The peak heat release rate (pHRR) of the FR-PET&PTFE TTENG fabric of Example 1 is 45.67 kW / m 2 , which is much lower than the FR-PET TTENG fabric of Comparative Example 4 (336.02kW / m 2 ); the total heat release (THR) of FR-PET&PTFE TTENG fabric is 5.31MJ / m 2 , compared with FR-PET TTENG fabric (THR is 6.97MJ / m 2 ), decreased by 23.7%. It can be seen that the composite yarn prepared with flame-retardant polyester filaments and PTFE filaments as the outer friction layer can reduce the generation of smoke during the combustion process.

[0110] Furthermore, each embodiment and comparative example was tested, and the summary results are shown in Table 3 below:

[0111] Table 3

[0112]

[0113]

[0114] Experimental Example 3

[0115] Electrical output performance

[0116] (1) The composite yarns in each embodiment and comparative example were woven into a fabric with a plain weave structure of 30 mm × 30 mm, grounded with a Keithley electrometer, and a periodic contact and separation motion was applied by a linear motor (fixed force of 60 N, frequency of 2 Hz). The open circuit voltage (V OC ), short circuit current (I SC ) and short-circuit charge (Q SC) to collect real-time data to test its electrical output performance; the results are as follows Figure 5-7 And as shown in Table 4.

[0117] Figure 5 , 6 The results show that the V OC =28V, I SC =390nA, Q SC =9nC; when the load resistance is 300MΩ, the maximum power density is 15.98mW·m -2 , excellent electrical output performance.

[0118] Figure 7 The results show that compared with the FR-PET TTENG in Comparative Example 4, the V OC ,I SC and Q SC The value is higher than that of Comparative Example 4, and the electrical output performance is better than that of the FR-T-TENG in Comparative Example 4, indicating that compared with the composite yarn prepared with only flame-retardant polyester filaments as the outer friction layer, the composite yarn prepared with flame-retardant polyester filaments and PTFE filaments as the outer friction layer can significantly improve the electrical output performance of the composite yarn. This is mainly because the fluorine group on the PTFE carbon chain has the strongest electron-accepting ability, which enhances the triboelectric electronegativity of the FR-PET TTENG surface, which is conducive to obtaining more negative charges in the contact charge with the acrylic plate, thereby resulting in the FR-PET&PTFE TTENG producing more surface charge density under pressure, showing higher point output performance.

[0119] Table 4

[0120]

[0121]

[0122] As shown in the table, V OC ,I SC and Q SC The value is lower than that of Comparative Examples 4 and 5, and the electrical output performance is excellent. Compared with Comparative Examples 4 and 5, it can be seen that the friction nano-power generation fabric prepared with flame-retardant polyester filaments and PTFE filaments as the outer friction layer can obtain more excellent electrical performance, and it is explained that selecting a specific ratio of the number of flame-retardant polyester filaments and PTFE filaments can improve the electrical output performance of the friction nano-power generation fabric.

[0123] Experimental Example 4

[0124] Mechanical properties

[0125] With reference to the method in standard GB / T3923.1-2013, the tensile strength of the friction nano-electricity generating fabrics obtained in the comparative examples of each embodiment was tested, and the results are shown in Table 5 below.

[0126] Table 5

[0127]

[0128] As shown in the table, the tensile strength of the fabric corresponding to Example 1 is significantly higher than that of Comparative Examples 1-5. It can be seen that the present invention uses flame-retardant polyester filaments and PTFE filaments as the outer friction layer to prepare friction nano-power generation fabrics, and the mechanical properties of the fabric can be improved by adjusting the root ratio and gear transmission ratio of the flame-retardant polyester filaments and PTFE filaments.

[0129] Experimental Example 5

[0130] Working stability of friction nanoelectricity fabric

[0131] The open circuit voltage of the friction nano-electric power generation fabric prepared in each embodiment and comparative example was tested before and after continuous beating 10,000 times, before and after washing 5 times, before being soaked in gasoline and after being soaked in gasoline and ignited-extinguished, and the open circuit voltage change rate was calculated.

[0132] Open circuit voltage change rate = | open circuit voltage before test - open circuit voltage after test | ÷ open circuit voltage before test × 100%

[0133] The calculated open circuit voltage change rate test results are summarized in Table 6 below:

[0134] Table 6

[0135] Group Continuous tapping 10000 times / % Wash 5 times / % Burning 5 minutes / % Example 1 0 2.3 39.52 Example 2 0 2.5 40.15 Example 3 0 1.9 46.07 Example 4 0 1.3 52.49 Example 5 0 2.5 35.78 Example 6 0 2.9 28.04 Example 7 0 3.2 20.71 Comparative Example 1 0.5 2.9 27.18 Comparative Example 2 0.6 3.2 21.30 Comparative Example 3 0.6 3.7 17.22 Comparative Example 4 0 3.6 15.40 Comparative Example 5 0 2.6 33.83

[0136] Experimental Example 6

[0137] Moisture permeability test

[0138] Referring to the detection method of ISO 15946 standard, the air permeability and moisture permeability of the friction nano power generation fabrics prepared in each embodiment and comparative example were tested. The results are shown in Table 7 below:

[0139] Table 7

[0140]

[0141]

[0142] Experimental Example 7

[0143] application

[0144] The fabric of Example 1 was worn on the joints of firefighters' limbs, and the degree of bending of their fingers (such as Figure 8 When the finger is bent, the open circuit voltage of the fabric changes significantly, and the open circuit voltage is significantly different at different bending angles, indicating that the friction nano-electricity generating fabric with good flame retardancy and smoke suppression provided by the present invention can monitor human body pressure and limb movement, thereby meeting the self-powered sensing requirements of the intelligent fire suit.

[0145] In addition, the friction nano-electricity generating fabric with good flame retardancy and smoke suppression provided by the present invention can be integrated into an intelligent escape carpet, and connected with an LED indicator light to construct a self-driven fire escape system for displaying the optimal escape route in real time under power outage conditions in the event of a fire. For those who cannot escape in time, they can generate electricity by walking or running to contact and separate from the carpet, thereby driving the indicator light to light up, and displaying the escape direction (such as Fig. 9 As shown in Figure 2). Since the fabric has self-extinguishing properties and high energy output after burning, it can work for a long time without the support of power resources under extreme fire conditions, showing broad application prospects in protecting life or property safety.

[0146] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A composite yarn, characterized in that: The invention has a skin-core structure, which is composed of an inner core and an outer friction layer. The inner core is a silver-plated nylon filament, and the outer friction layer includes a flame-retardant polyester filament and a polytetrafluoroethylene filament.

2. The composite yarn according to claim 1, characterized in that In one composite yarn, the total number of the flame-retardant polyester filaments and the polytetrafluoroethylene filaments is 8, and the flame-retardant polyester filaments and the polytetrafluoroethylene filaments are selected from 1 to 7, respectively.

3. The composite yarn according to claim 2, characterized in that In one of the composite yarns, the number of the flame-retardant polyester filaments is 4 and the number of the polytetrafluoroethylene filaments is 4, or the number of the flame-retardant polyester filaments is 3 and the number of the polytetrafluoroethylene filaments is 5.

4. The composite yarn according to claim 1, characterized in that The fineness of the silver-plated nylon filament is 20-200D, the fineness of the flame-retardant polyester filament is 50-200D, and the fineness of the polytetrafluoroethylene filament is 300-600D.

5. The composite yarn according to claim 1, characterized in that The flame-retardant polyester filament comprises a polymerized monomer, MOFs and a flame retardant; the amount of the MOFs is 1-5% of the mass of the polymerized monomer, and the amount of the flame retardant is 0.5-5% of the mass of the polymerized monomer; the flame retardant is selected from any one or more of a carbon-based flame retardant, a phosphorus-based flame retardant and a nano-inorganic flame retardant.

6. The method for preparing the composite yarn according to any one of claims 1 to 5, characterized in that: The steps include: The flame-retardant polyester filament and PTFE filament are pre-wound on the yarn tube, and the silver-plated nylon filament is wound on a special bobbin in the middle of the high-speed braiding machine, fed axially from under the track disk, the gear transmission ratio is set, and then the machine is turned on for spinning to obtain a composite yarn with a skin-core structure.

7. The preparation method according to claim 6, characterized in that: The gear transmission ratio is 0.3-0.

5.

8. The preparation method according to claim 7, characterized in that: The gear transmission ratio is 0.3-0.

35.

9. A friction nano-electricity generating fabric with good flame retardancy and smoke suppression, characterized in that: The composite yarn is woven from the composite yarn described in any one of claims 1 to 5 or the composite yarn prepared by the preparation method described in any one of claims 6 to 8.

10. Application of composite yarn or friction nano-electricity generating fabric with good flame retardancy and smoke suppression in smart firefighting suits and smart escape carpets, characterized in that: The composite yarn is the composite yarn described in any one of claims 1 to 5 or the composite yarn prepared by the preparation method described in any one of claims 6 to 8; the friction nano-power generation fabric with good flame retardancy and smoke suppression is the friction nano-power generation fabric with good flame retardancy and smoke suppression described in claim 9.